Tasa de crecimiento y composición química de los pastos Tanzania y Mombasa (Megathyrsus maximus) en época seca y lluviosa. - Cevallos Guamán, Evelyn Andrea (2022)
The production of pastures and forages as the main source of raw material for livestock production, is about solving the problem about solving the problem about the lack of knowledge of the chemical composition of pastures at the foliar level and the growth rate. The objective was to evaluate the growth rate and chemical composition of Tanzania and mombaza grasses (Megathyrsus maximus) at the Sacha Wiwa Experimental Center. Six pasture plots were used, with four treatments and six replications, applying a completely randomized block design and Tukey´s multiple range test at 5 % probability. Soil and foliar laboratory analyzes were carried out to determine the chemical composition at the foliar level in its different stages of maturity. At 45, 60 and 75 days, growth variables such as plant height (cm), leaf length and width (cm) and forage production (Kg/FV) were evaluated during the dry and rainy seasons. The results obtained were regarding the height of the plant was obtained by the Tanzania grass at 75 days with 200,67 cm, in terms of the width and length of the leaf it was obtained by the Mombasa grass at 60 days with 3,78 cm and 147,17 cm respectively, of the same forage production Mombasa grass at days with 1,90 Kg/FV values that are reflected in the dry season. In the foliar chemical composition, the macroelements N, P, Ca obtained better results for the two cultivars during the two seasons of the year. The grass with the highest growth rate was the Mombasa cultivar during 45, 60 y 75 days.